HAK ASIMILASI BAGI NARAPIDANA DI LEMBAGA PEMASYARAKATAN - TITIN TITAWATI (Universitas Mahasaraswati K. Mataram, 2024)
This research is based on about what is the giving process ? right assimilation for prisoners in correctional institutions. The aim of this research is to find out the procedures and obstacles in granting assimilation rights to prisoners in correctional institutions. Study This will analyze granting assimilation rights, And factors Which become inhibitor in giving assimilation rights.Results from study This is How procedure giving right assimilation for prisoner And constraint Which There is. So that right assimilation Which they accept can walk effective And efficient in accordance objective from assimilation the . Based on results And discussion , found obstacles in giving right assimilation , and the cause . So that in the future each each institution correctional can notice obstacles that exist to granting right assimilation to prisoner walk with Good And get results in accordance with which are desired